Pemanfaatan Kain Ulos dalam Fashion Modern: Kajian Literature Review tentang Pelestarian Budaya dan Industri Kreatif - Afiqah Dwy Puspita; Saqinatuzzahra Saqinatuzzahra; Syakira Maliha Wardana; Dina Ampera; Untung Desy Purnamasari (Alpatih Harapan Semesta, 2026)
Kain Ulos is one of the cultural heritages of the Batak community that has symbolic values and philosophical meanings in traditional life. Along with the development of modernization, the use of ulos cloth has changed from traditional ceremonial fabric into part of modern fashion. This study aims to determine the utilization of ulos cloth in modern fashion as an effort to preserve Batak culture in the modernization era. The research method used is a literature review by examining various written sources such as journals, books, and scientific articles related to the research topic. Data collection was carried out using the content analysis method through reviewing various literature sources. The results of the study indicate that the application of ulos cloth in various modern fashion products such as ready-to-wear clothing, outerwear, skirts, bags, and accessories can increase public interest, especially among younger generations, in using traditional fabrics. Besides contributing to cultural preservation, the use of ulos in modern fashion also has a positive impact on the development of the creative industry and the economy of local craftsmen. Therefore, fashion design innovations using ulos cloth need to continue to be developed while still paying attention to the cultural values and symbolic meanings contained in each ulos motif.